Poor pathogenetic role of luminal obstruction in the development of appendicitis: A case report. Issue 15 (April 2018) - Giudici, Francesco; Scaringi, Stefano; Zambonin, Daniela; Voglino, Costantino; Messerini, Luca; Ficari, Ferdinando; Bechi, Paolo
Abstract: Rationale: In developed countries, the incidence of acute appendicitis is about 95 cases out of 100, 000 per year, being one of the most common urgencies in general surgery worldwide. However, its pathogenesis is still poorly understood. Direct luminal obstruction (by a fecalith, lymphoid hyperplasia, or impacted stool) is reported to be the primary and principal cause of acute appendicitis. Patient concerns: During October 2016 a 58-year-old woman was operated because of a clinical recurrence of Crohn's disease. At surgery, performed through single incision laparoscopy, we observed an exceptional finding. Diagnoses: Despite a previous ileo-cecal resection, the appendix was still present and vascularized by small vessels within the mesoappendix connected to the neo-terminal ileum mesentery; it was about 5 cm long and macroscopically not inflamed even if its base was clearly no longer connected with the cecum. Outcomes: The patient underwent ileo-colic resection with en-bloc removal of the appendix. With a narrow metallic stylet probe we carefully tried to enter the appendix lumen through the opposite side from its fundus but we were not able to enter it before cutting the wall with scissors. Pathological examination confirmed the Crohn's disease recurrence affecting the small bowel and the appendix lumen obstructed in the presence of a fecalith but without any sign of inflammation. Lessons: This finding seems to highlight the poor pathogenetic role of luminal obstruction in the development of acute appendicitis.